Optimizing Tiktok Shop as a Marketing Strategy to Increase Sales MSME in Sidoarjo - Mukhlasin, Fernanda Aurellia Putri; Utami, Anisa Fitria; Taufiq, M. (Unram Journal of Community Service, 2025)
MSMEs in Sidoarjo Regency are now increasingly competitive thanks to TikTok Shop optimization training as a digital marketing tactic. The purpose of this program is to increase sales conversion rates, promote MSME products online, and improve MSME participants' digital literacy in using the TikTok Shop e-commerce platform. The three main phases of training include registering for TikTok Shop, optimizing product uploads, and practicing digital marketing tactics. Based on the training findings, 90% of participants succeeded in optimizing product uploads, 80% succeeded in implementing efficient digital marketing methods, and 100% of participants succeeded in creating TikTok Shop accounts. When compared to previously using TikTok Shop, the majority of MSMEs experienced an increase in turnover of 50% to 100%, and some business actors even reported an increase in turnover of more than 100%. Through multi-platform marketing integration, this program has succeeded in helping MSMEs increase their product visibility, despite obstacles in creating attractive content and optimizing product keywords. The TikTok Shop platform's ability to reach the MSME market in the digital era is shown by an average product population growth of 70%.